MODELLING OF FANO RESONANCE IN NANOSTRUCTURED MATERIAL - Puchkov, Nikolai; Vanin, Aleksander; Solovyev, Vladimir (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2016)
Optical properties of novel nanostructured material Ag / opal have been modelled on the basis of the Bragg diffraction and the Fano resonance between diffracted in Ag / opal composite photonic crystal electromagnetic waves and those resonantly scattered by silver dendrites